The Federal Reserve System Balance Sheet : What Happened and Why it Matters - Stella, Peter (Washington, D.C. : International Monetary Fund, 2009)
The recent expansion of the balance sheet of the consolidated Federal Reserve Banks (FRB) is analyzed in an historical context. The analysis reveals that the nature of Fed involvement in U.S. financial markets has changed dramatically and its expansion is several orders of magnitude beyond what is usually reported. The associated fiscal risks and potential exit strategies are then considered. Although risks are considerable in certain unlikely scenarios, FRB capital, earnings capacity, and reserves are more than ample to preserve their financial independence. Nevertheless, the occurrence of losses or a significant drop in FRB profit might lead to an eventual curtailment of Fed operational independence. The paper concludes by considering options to enhance FRB risk management and to assign responsibilities for monetary, financial stability and fiscal policies once the current crisis is overcome.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet